The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/mnras/stab3378
|View full text |Cite
|
Sign up to set email alerts
|

Velocity monitoring of γ Cas stars reveals their binarity status

Abstract: The binary status of γ Cas stars has been discussed while theoretically examining the origin of their peculiar X-ray emission. However, except in two cases, no systematic radial velocity monitoring of these stars had been undertaken yet to clarify their status. We now fill this gap using TIGRE, CARMENES, and UVES high-resolution spectroscopy. Velocities were determined for 16 stars, revealing shifts and/or changes in line profiles. The orbit of six new binaries could be determined: the long periods (80–120 d) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 90 publications
(115 reference statements)
4
36
0
Order By: Relevance
“…6). Moreover, for the TIGRE spectra, overall Hα RVs were determined by four different methods (for details, see Nazé et al 2019aNazé et al , 2022a: the first-order moment of the entire line profile, a comparison between the blue wing and the mirrored red wing 7 obtained by reversing the velocities, correlation of the line profile to a two-Gaussian function (bisector derivation at half width), and correlation of the observed profiles against the profile obtained on February 19, 2021. The results of all these measurements are displayed in the middle and bottom panels of Fig.…”
Section: Radial Velocitiesmentioning
confidence: 99%
“…6). Moreover, for the TIGRE spectra, overall Hα RVs were determined by four different methods (for details, see Nazé et al 2019aNazé et al , 2022a: the first-order moment of the entire line profile, a comparison between the blue wing and the mirrored red wing 7 obtained by reversing the velocities, correlation of the line profile to a two-Gaussian function (bisector derivation at half width), and correlation of the observed profiles against the profile obtained on February 19, 2021. The results of all these measurements are displayed in the middle and bottom panels of Fig.…”
Section: Radial Velocitiesmentioning
confidence: 99%
“…Indeed, two Cas stars have long been known to lie in a binary system: Cas (Harmanec et al 2000) and Aqr (Bjorkman et al 2002). The multiplicity of other Cas analogs has been recently studied (Nazé et al 2022a). In total, orbits could be derived in eight cases (out of 25 Cas objects) and five additional stars show hints of binarity.…”
mentioning
confidence: 99%
“…Over the last eight years, we have used TIGRE to monitor the optical spectra of a sample of γ Cas stars. Thanks to its robotic mode, TIGRE enabled us to collect well-sampled time series of spectra which were used to perform a systematic radial velocity monitoring of these stars (Nazé et al, 2022). This study showed that the properties of the known and newly found γ Cas binaries do not significantly differ from those of other Be binary systems and that companions are of low mass (0.6 -1 M ).…”
Section: Hot Starsmentioning
confidence: 91%